Driving Change? Exploring the Role of Socio-Technical Experiments in Shaping Autonomous Mobility Transitions - Tim Fraske; Annika Weiser; Maximilian Schrapel; Jens Schippl; Daniel J. Lang; Alexey Vinel (ZBW – Leibniz Information Centre for Economics, 2024)
This systematic literature review inquires into the role of socio-technical experiments for autonomous driving and their potential to shape mobility transitions towards sustainability. As an emerging technology in an early stage of transition, AVs are increasingly being tested in different spatial contexts with diverse actor constellations in order to enhance the technology further. This article critically examines the added value of these experiments, how they affect the scaling-up of autonomous driving, and highlights key themes that researchers and practitioners should consider when designing experiments. The most striking aspect of our sample is the lack of continuous participatory methods, as well as weak linkages to the transition literature. We conclude with central findings that emerged as future research avenues for the topic, such as the need to overcome projectification in the design process of the experiments, a more nuanced perspective on sustainability issues and place-related factors, and implications for local governance.
Keywords: C93; O33; Q56; R00; 330; sustainability transitions; mobility; autonomous vehicles; socio-technical system